Migration and accumulation of crude oils from Permian lacustrine source rocks to Triassic reservoirs in the Mahu depression of Junggar Basin, NW China: Constraints from pyrrolic nitrogen compounds and fluid inclusion analysis. (November 2016) - Liu, Guangdi; Chen, Zhelong; Wang, Xulong; Gao, Gang; Xiang, Baoli; Ren, Jiangling; Ma, Wanyun
Highlights: Pyrrolic N compounds in crude oils of Mahu depression were examined. Oil migration in slope and depression area is different from fault belts. Fluid inclusion petrography and microthermometry show two stages of oil accumulation. FTIR provides evidence of different oil sources. Migration and accumulation process model has been established. Abstract: The geochemical compositions of crude oils and Permian source rocks from the Mahu depression of the Junggar Basin were analyzed in this study. Based on tricyclic terpanes and isoprenoid biomarkers, three oil groups (I, II and III) can be identified that correspond to different source rock formations and organic facies. After examination of the influence of source facies and thermal maturity, and selected biomarker ratios based on carbazole isomers such as 1-MC/4-MC, 1, 8-DMC/2, 7-DMC and [a]/([a] + [c])-BC ratios in different oil groups, allowed us to determine the direction of hydrocarbon migration in different reservoirs. In addition, abundant oil inclusions are present with fluorescence colors ranging from yellow to blue-white. These were analyzed by FTIR to distinguish between different sources for the oils. Fluid inclusion petrography and microthermometry were also used to prove two stages of oil migration and their different sources. Taking into consideration possible migration pathways and likely driving forces, we conclude that abnormally high pressure in the Permian sequence acted as the main driving force for oil migration. The major migration pathways were vertical faults in the fault belts and slope areas, and sand bodies in the deeper areas. Group I1 oils from P1 f carbonate source rocks in the fault belts mainly migrated vertically through the faults and accumulated in T1 b reservoirs in the Late Triassic, and were driven by excess formation pressure and buoyancy. Group I2 oils in the slope areas first migrated vertically within thrust faults from P1 f mudstone source rock in the Late Triassic, after which they migrated laterally over short distances to accumulate in T1 b sand bodies. Group II oils from adjacent P2 w source rocks in the center of the depression migrated mainly in the Late Jurassic, due to abnormally high pressure, and accumulated in nearby T1 b traps. Some reservoir rocks in the slope area contain two generations of fluid inclusions, implying oil mixing from early-stage P1 f oils and late-stage P2 w oils, resulting in the group III oils. Combining these data from biomarkers, pyrrolic nitrogen compounds and fluid inclusions allowed us to construct models of migration and accumulation for oils in the Mahu depression.